Attitudes of Nursing Students towards Suicide Prevention: A Study from Central India - Ghormode, Deepak; Gupta, Pramod; Ratnani, Devendra; Singh, S. K. (International Journal of Innovative Research in Medical Science, 2018)
Background: Managing patients with suicide attempts effectively requires overcoming barriers to their care. The attitudes and beliefs of the healthcare professionals have significant effect on the outcome of the treatment and implementation of the preventive strategies. Objectives: Aim of the study was to assess the attitude of nursing students toward suicide prevention. Materials and Methods: The study had a cross sectional design of 284 nursing students who were randomly recruited from the two institutions. Attitude toward suicide prevention scale was administered. Results: Most were young single females, from rural locality, who were pursuing either BSc Nursing or GNM courses. Very few had previous exposure to suicide prevention training programmes. Nearly half of the students showed favourable attitude towards patients with suicidal attempt, considering it as their responsibility and their efforts as rewarding. Nearly half students also showed empathy towards these patients not considering the attempts as just attention seeking ones. Nearly one third were uncertain whether the patients reveal their plans of attempt and whether the suicide prevention measures were draining of the resources. Half of the subjects showed pessimism towards modifying the risk factors of unemployment and poverty. Conclusions: Only half of the nursing students showed favourable attitude working with patients with suicide attempts. More educational and training programs on suicide prevention are therefore needed in these students for better prevention and management of these patients.